Effect of Different Extraction Methods on the Quality and Biochemical Attributes of Pomegranate Juice and the Application of Fourier Transformed Infrared Spectroscopy in Discriminating Between Different Extraction Methods - Arendse, Ebrahiema; Nieuwoudt, Helene; Fawole, Olaniyi Amos; Opara, Umezuruike Linus (Frontiers in Plant Science, 2021)
This study investigated the effects of extraction methods on the physicochemical, phytochemical and antioxidant properties of pomegranate juice (cv. Wonderful). In addition, the application of attenuated total reflectance Fourier transformed infrared (ATR FT-MIR) spectroscopy and chemometrics was explored in order to discriminate between different extraction methods. Juice variants evaluated included juice extracted without crushing the seeds (arils only) using a juice extractor (JE), juice extracted by crushing the seeds using a blender (arils plus seed) (JB) and juice extracted from half fruit using commercial hand press juicer (CH). Juice extracted from CH had higher total soluble solid (TSS) content (18.20%), TSS:TA ratio (15.83), color properties (a* = 32.67, b* = 11.80, C* = 34.77), lower titratable acidity (1.19%) and cloudiness (0.18). The juice extracted from JB, showed the highest titratable acidity (2.17%), cloudiness (0.43) and lowest pH value (2.69). The total phenolics, and anthocyanin content in the investigated juice ranged from 1.87 to 3.04 grams gallic acid equivalent/L and 37.74 to 43.67 mg cyanidin 3-glucoside equivalent/L of crude juice, respectively. Juice extracted from JB and CH was significantly higher in phenolic and anthocyanin compared to JE. Orthogonal partial least squares discriminant analysis (OPLS-DA) and principal component analysis (PCA) was used for classification. Classification accuracy of 100% was achieved between the three methods. The S-line plot revealed that the corresponding wavelength bands within the following region 1090, 1250, 1750, and 3200 cm-1 were responsible for discrimination between the different extraction methods. Our results suggest that the main contributor to the discrimination between extraction methods were TSS, TSS:TA, color attributes and anthocyanin content. Overall, this study has demonstrated that ATR FT-MIR spectroscopy provides a powerful way to discriminate between juice extraction methods.